Acute HAV Infected Patient's Distribution According to Age and Sex in Wasit Province/Iraq. - A. Jassim, Ali; M.Utba, Nawal; J. Mohammed, Wisam (Iraqi Journal of Science, 2023)
Hepatitis A virus infection occurs globally and is causing a public healthconcern, primarily in developing countries due to its persistent circulation in theenvironment. A total of 120 individuals were included in this study, anti-HAV IgMantibodies were detected in serum of 100 individuals of them (patients group) whoattended the Wasit central public health laboratory from different cities in WasitProvince, Iraq, during the period from November 2013 to March 2014.Whileanother 20 individuals were considered as control group which anti – HAV IgMantibody was negative in their serum.Acute infection is confirmed by detection of IgM anti–hepatitis A virus (HAV),which appears early in the course of infection, anti-HAV IgM antibodies weresignificantly higher (P<0.001) in hepatitis A patients than control using a solidphase, two-step incubation, antibody capture ELISA kit .Most of the HAV patients were located within the first decade (1-10 years) with apercentage of 91%, whereas 9% of all patients were within second decade (10-20years). In this study, HAV infection is distributed equally among genders. Therefore,there was no significant difference between females than male with a ratio of (1female: 0.786 male) and percentage of 56% females than 44% males.The aim of the study is to determine the distribution of acute HAV infection withage and sex of the infected patient in Wasit province/ Iraq.